Photosynthesis in The Qur'an: A Comparative Study of The Interpretation of The Science of The Ministry of Religion of The Republic of Indonesia and The Interpretation of The Verses of Al-Kauniyah Fi Al-Qur'an Al-Karim By Zaghlul An-Najjar - Wahyu Nur Sinta Sari; Kharis Nugroho; Yeti Dahliana; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the concept of photosynthesis as described in the Qur'an. The research examines verses that reference plant life, such as Surah Al-An’am: 99, and analyzes their relevance to the process of photosynthesis, which involves chlorophyll, sunlight, and the production of oxygen. Through a comparative approach, the study contrasts two interpretations: the Ministry of Religion’s Tafsir Ilmi, which combines traditional exegesis with scientific insights to highlight the symbiotic relationship between faith and science, and Zaghlul An-Najjar’s Tafsir Ayat Al-Kauniyah, which delves into specific scientific elements within the Qur'anic text. This study emphasizes how both interpretations seek to reconcile religious teachings with modern scientific understanding, providing readers with a multifaceted view of how photosynthesis is portrayed in Islamic scripture. It highlights key verses linking natural processes to divine creation, suggesting that scientific phenomena like photosynthesis are aligned with Islamic teachings on the interdependence between nature and spirituality. The findings underscore the Qur'an’s relevance to contemporary science and its potential to inspire deeper ecological awareness within the framework of religious belief.